DI PROPINSI SUMATERA UTARA - Nizmah Oktoviana, Abubakar Hamzah, Sofyan Syahnur. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2015)
Abstract:: The purpose of this study was to determine the performance of the economic, social and environmental as well as the interaction area for suitability Serdang Bedagai as one strategic district area in North Sumatera Province. The method used in this research is the analysis method typology klassen, analysis of location quotient, shift share analysis, schallogram, gravity analysis, and analysis of geographic information systems (GIS). The data used is data GDP, population, the type and number of facilities regency/cities, the distance between the regency/city. As the comparison area is the entire regency that the area had the same declaration with Serdang Bedagai District and North Sumatera as a reference region. The results of the analysis of economic performance shows Serdang Bedagai contributed to the GDP of Province and the economic growth of the largest average. Based on the typology Klassen is a growing area, the sector basis (LQ>1) is the agricultural sector, construction sector, mining and quarrying. Analysis by the method of shift-share estaban-marquillas show that with the effect of allocation, agricultural sector have competitive value, but has yet to have a value of specialization. Aggregate showed a positive shift towards all sectors as indicated by the positive value of Dij. The results of the analysis are Serdang Bedagai schallogram is the hierarchy I and the analysis of the interaction of gravity has a more tightly. Performance in social and environmental analysis has increased with population growth, education, employment, health, poverty and protected areas and coastal conditions. Based on the analysis and GIS suitability analysis concluded that Bedagai Serdang potential to be one of the strategic areas in the district of North Sumatera Province. Expected policy implication is the attention to the agricultural sector, supported by the development of agro-industries. Keywords: Strategic Area, Typology Klassen, Location Quotient, Shift Share Estaban- Marquillas, Schallogram, The Interaction Region, Geographic Information System Abstrak: Tujuan penelitian ini adalah untuk mengetahui kinerja ekonomi, sosial dan lingkungan serta interaksi daerah untuk kesesuaian Kabupaten Serdang Bedagai sebagai salah satu kawasan strategis kabupaten di Propinsi Sumatera Utara. Metode yang digunakan dalam penelitian ini adalah metode analisis tipologi klassen, location quotient, shift share, skalogram, gravitasi, dan analisis sistem informasi geografis (SIG). Dengan menggunakan data PDRB, jumlah penduduk, jenis dan jumlah fasilitas kabupaten/kota, jarak antar kabupaten/kota. Dengan daerah pembanding adalah kabupaten yang seumur dengan Kabupaten Serdang Bedagai dan Propinsi Sumatera Utara sebagai daerah referensi. Hasil analisis kinerja ekonomi menunjukkan Kabupaten Serdang Bedagai memberikan kontribusi terhadap PDRB Propinsi dan mengalami pertumbuhan ekonomi rata-rata terbesar. Berdasarkan tipologi klassen merupakan daerah berkembang, sektor basis (LQ>1) adalah sektor pertanian, sektor bangunan, sektor pertambangan dan penggalian. Analisis shift share estaban-marquillas menunjukkan bahwa dengan adanya pengaruh alokasi, sektor pertanian mempunyai nilai kompetitif, namun belum memiliki nilai spesialisasi serta menunjukkan pergeseran yang positif terhadap semua sektor yang ditunjukkan dengan nilai Dij yang positif. Hasil analisis skalogram adalah Kabupaten Serdang Bedagai berada pada hirarki I dan dengan analisis gravitasi memiliki interaksi daerah yang lebih erat. Kinerja dibidang sosial dan lingkungan mengalami peningkatan yang dianalisis dengan pertumbuhan penduduk, pendidikan, ketenagakerjaan, kesehatan, kemiskinan serta kondisi kawasan lindung dan pesisir. Berdasarkan hasil analisis dan kesesuaian analisis SIG disimpulkan bahwa Kabupaten Serdang Bedagai berpotensi untuk menjadi salah satu kawasan strategis kabupaten di Propinsi Sumatera Utara. Implikasi kebijakan yang diharapkan adalah perhatian terhadap sektor pertanian yang didukung dengan pengembangan agroindustri. Kata kunci : Kawasan Strategis, Tipologi Klassen, Location Quotient, Shift Share Estaban-Marquillas, Skalogram, Interaksi Daerah, Sistem Informasi Geografis.